Grain yield of maize hybrids at two plant densities with and without tillers removal Rendimento de grãos de híbridos de milho em duas densidades de plantas com e sem a retirada dos perfilhos - Schmitt A.* (2009)
Maize does not have an effective mechanism to compensate empty spaces in the field. Therefore, tillering hybrids may be more efficient to use environmental resources, especially under low plant populations. This reserach was carried out aiming to evaluate the agronomic performance of maize hybrids grown at two plant densities, with and without tiller's presence. The experiment was set in Lages, SC, Brazil, during the 2005/2006 and 2006/2007 growing seasons. Three hybrids were tested: AS 1560, Penta and P30F53. Each hybrid was evaluated at the densities of 4 and 7pl m-2, keeping tillers until harvest or removing them when the crop had nine expanded leaves. The percentage of plants with tillers at four growth stages, grain yield and yield components were assessed. Hybrids P30F53 and AS 1560 produced more tillers than Penta at the density of 4pl m-2. Tillers destiny did not affect grain yield during the first growing season. In 2006/2007 tiller maintenance promoted higher grain yield than tiller removal for all hybrids at the lower plant density. The results of this work showed that tiller removal does not enhance maize agronomic performance. Furthermore, they demonstrated that tiller maintenance may increase grain yield when maize is grown under low plant densities.